Coordinate regulation of pp90rsk and a distinct protein-serine/threonine kinase activity that phosphorylates recombinant pp90rsk in vitro. - Chung, J (1991)
Protein kinase assays that use recombinant pp90rsk as a substrate were developed in an attempt to identify growth-regulated enzymes responsible for the phosphorylation and activation of pp90rsk S6 phosphotransferase activity. With this assay we have ientified a pp60v-src-, growth factor-, phorbol ester-, and vanadate-regulated serine/threonine protein kinase activity that is not related to two other cofactor-independent, growth-regulated protein kinases, pp70-S6 protein kinase and pp90rsk. The pp90rsk-protein kinase activity (referred to as rsk-kinase) is also not related to cofactor-dependent signal transducing protein kinases such as the cyclic AMP-dependent protein kinases, members of the protein kinase C family, or other Ca2(+)-dependent protein kinases. In vitro, partially purified rsk-kinase phosphorylates several of the sites (serine and threonine) that are phosphorylated in growth-stimulated cultured cells. A detailed examination of the mitogen-regulated activation kinetics of rsk-kinase and pp90rsk activities demonstrated that they are coordinately regulated. In addition, protein kinase C is not absolutely required for epidermal and fibroblast growth factor-stimulated activation of rsk-kinase, whereas, like pp90rsk, platelet-derived growth factor- and vanadate-stimulated rsk-kinase activity exhibits a greater dependence on protein kinase C-mediated signal transduction. The characterization and future purification of the rsk-kinase(s) will improve our understanding of the early signaling events regulating cell growth.